Análise de projetos de nanocircuitos plasmônicos lineares em nanoantena de microfita retângular em grafeno no software Comsol - MIRANDA, Keila Alves (2018)
In this work, an analysis of nanoantena graphene rectangular microfita type using COMSOL Multiphysics commercial software 4.2a, for solution of differential equations by numerical analysis of the finite element method will be performed. The simulations will analyze the main characteristics of antenna radiation, ranging from the electric field, input impedance, the reflection coefficient, input power and current density, thus having a good idea of the behavior of such an antenna operating in the range of THz. If you want to collaborate to design studies of resonant structures.